From Molecules to Materials, Devices and Processes: The Chemical Basis of Novel Technologies - Giuseppina Raffaini; Fabio Ganazzoli (Molecules)
This Special Issue was launched in connection with the joint XIII National Congress of AICIng (the Italian Association of Chemistry for Engineering) and the II National Congress of the Division of Chemistry for the Technologies of the Italian Chemical Society, held at the Politecnico di Milano (Italy) from 25 to 28 June 2023 [...]